Biodegradation and metabolic fate of thiamphenicol via Chlorella sp. UTEX1602 and L38. (January 2020) - Song, Chunfeng; Wei, Yanling; Sun, Jiasi; Song, Yingjin; Li, Shuhong; Kitamura, Yutaka
Graphical abstract: Highlights: Thiamphenicol can be effectively removed (up to 97%) via Chlorella sp. Biodegradation contributed around 97% of the total removal efficiency. The half-lives of TAP could be controlled low to 3.2 d. Metabolic pathways are chlorination, chlorine substitution, dehydration and hydroxylation. Abstract: Thiamphenicol (TAP) is a typical medicament in animal husbandry and aquaculture for treating diverse infections. In this work, thiamphenicol biodegradation performance via microalgae was tested. The cultivation results showed that TAP could be biodegraded via the target algae. Chlorella sp. L38 presented strong adaptive ability to high concentration TAP. Biodegradation, biosorption and bioaccumulation were the dominant metabolic fates. Biodegradation contributed around 97% of the total removal efficiency at the TAP concentration of 46.2 mg·L −1 . The removal of TAP by Chlorella L38 and UTEX1602 agreed with the kinetic range of zero-order reaction, and the shortest half-lives were 3.2 d and 5.0 d. Based on the identification of metabolites, the metabolic pathway of TAP by microalgae was proposed, including chlorination, chlorine substitution, dehydration and hydroxylation. Therefore, biological treatment via microalgae has the potential for TAP purification.